Dietary magnesium intake is protective in patients with periodontitis - Li, Xin-yu; Wen, Ming-zhe; Liu, Hui; Shen, Yu-chen; Su, Li-xin; Yang, Xi-tao (Frontiers in Nutrition, 2022)
Background Periodontitis is a chronic inflammatory disease of the oral cavity characterized by inflammation of the periodontal tissue and resorption of the alveolar bone, which has a high incidence and is the main cause of tooth loss in adults. In addition to its role in promoting osteogenesis, magnesium also has a role in regulating the inflammatory response, both systemically and locally. There is growing evidence that magnesium is an important factor in maintaining the normal functioning of the body's immune system. Hypomagnesaemia can lead to a variety of chronic inflammatory diseases throughout the body, including periodontitis. Two-thirds of the US population suffers from magnesium deficiency. The connection between dietary magnesium and periodontitis is unknown. As a result, we set out to investigate the link between dietary magnesium intake and periodontitis. Methods In this study, we collected data from the National Health and Nutrition Examination Survey (NHANES) database from 2013 to 2014. Through 24-h dietary recalls, information about food consumption was collected. We examined the association between the dietary magnesium and periodontitis using multivariable logistic regression model. Based on odds ratios (OR) and 95% confidence intervals (CIs), a strong association was detected. Results Multivariable logistic regression analysis showed that the OR for periodontitis comparing the highest to the lowest quintile of dietary magnesium intake was 0.69 (95% CIs = 0.52~0.92). The restricted cubic spline (RCS) analysis showed that the non-linear association between dietary magnesium and periodontitis was statistically significant and that dietary magnesium supplementation reduced the prevalence of periodontitis. Conclusion Dietary magnesium intake is associated with the prevalence of periodontitis. Dietary magnesium deficiency increases the prevalence of periodontitis.